2020
DOI: 10.1088/1755-1315/411/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

The demand for beef in Indonesian urban

Abstract: The low consumption of animal protein food is one of the causes of the increasing number of stunting in Indonesia. This study analyzes the effect of changes in prices and incomes on demand for five animal food groups, namely fish, chicken, beef, eggs, and milk. The demand function approach uses the Almost Ideal Demand System model with the parameter estimates using Seemingly Unrelated Regression. The research data using 124,513 households from Indonesian National Socio-economics Survey in 2016. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The elasticities estimated in this study are comparable with the recent estimates by Arifin et al (2018) and Anindita et al (2020) who also used AIDS models, and found beef to be a price elastic commodity. The slight differences in the estimated compensated and uncompensated elasticities of this study might be due to fact that the other studies did not distinguish between domestic and imported beef, as opposed to this study.…”
Section: Research Questionsupporting
confidence: 90%
See 4 more Smart Citations
“…The elasticities estimated in this study are comparable with the recent estimates by Arifin et al (2018) and Anindita et al (2020) who also used AIDS models, and found beef to be a price elastic commodity. The slight differences in the estimated compensated and uncompensated elasticities of this study might be due to fact that the other studies did not distinguish between domestic and imported beef, as opposed to this study.…”
Section: Research Questionsupporting
confidence: 90%
“…A few earlier studies investigated beef demand in Indonesia; however, such research studies that apply the AIDS model are scarce (Arifin et al 2018;Anindita et al 2020). Further, the studies used different data sets, commodity coverage and independent variables and mainly employed estimation methods other than AIDS.…”
Section: Research Questionmentioning
confidence: 99%
See 3 more Smart Citations